Preliminary results of an integrated Petrographic, Chemical and Organic Residue Analysis of Neolithic pottery from Makhvilauri - Chkhatarashvili, Guram; Tskvitinidze, Nikoloz; Beridze, Giorgi; Javakhishvili, Irakli; Vekua, Rezo; Rogava, Andria; Olet, Lilly; Wiltshire, Isabel L.; Cramp, Lucy; Roffet-Salque, Melanie (Revista Arheologică, 2026)
In recent years, extensive archaeological and laboratory investigations have been conducted at prehistoric sites in southwestern Georgia. The integrated analysis of data obtained through interdisciplinary research has made it possible to develop a clearer understanding of ancient human activities, stone-processing technologies, climatic conditions, mobility patterns, chronology, and other aspects of prehistoric life. Within the assemblage from the Neolithic settlement of Makhvilauri, pottery occupies a prominent place. From a typological perspective, vessel bases are particularly informative, as they clearly preserve traces of use. The present study provides the first comprehensive analysis of the Neolithic ceramic assemblage from Makhvilauri, carried out in laboratories in Georgia and abroad. For this research, two ceramic fragments dated to the 7th-6th millennia BCE were selected. The investigations have made it possible to draw several important preliminary conclusions, which lay the foundation for future research involving a larger number of ceramic samples.